2022
DOI: 10.1039/d2tc03304f
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic hybrid self-pigmenting effect of anodic aluminium oxide membranes

Abstract: Anodic aluminium oxide (AAO) membranes with hexagonally packed nanochannel arrays have been utilized as a promising template to develop functional nanostructures. The characteristics of the AAO membranes are crucial to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The microchannel system used by Liu et al, [8] to study the strong interaction between Ru/defects-rich aluminium oxide which boosts the photothermal methanation of carbon dioxide. Afterwards, Zhang [9] and Manogar [10] explored the organic-inorganic hybrid self-pigmenting effect on the antimicrobial activity of aluminium oxide nanoparticles using Lyngbya majuscule extract, while Raza [11] conducted research on the unsteady incompressible flow of magnetized aluminium oxide and titanium oxide nanoparticles by using blood as base fluid. Wahab et al, [12] used the aluminium oxide-based electrochemical sensor to detect highly efficient organosulfur compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The microchannel system used by Liu et al, [8] to study the strong interaction between Ru/defects-rich aluminium oxide which boosts the photothermal methanation of carbon dioxide. Afterwards, Zhang [9] and Manogar [10] explored the organic-inorganic hybrid self-pigmenting effect on the antimicrobial activity of aluminium oxide nanoparticles using Lyngbya majuscule extract, while Raza [11] conducted research on the unsteady incompressible flow of magnetized aluminium oxide and titanium oxide nanoparticles by using blood as base fluid. Wahab et al, [12] used the aluminium oxide-based electrochemical sensor to detect highly efficient organosulfur compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Highly ordered anodic porous alumina, which has a nanohoneycomb structure composed of uniform-sized cylindrical pores, has attracted much attention as a key material for fabricating various functional devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] If highly ordered anodic porous alumna can be directly formed on substrates such as Si wafers and indium tin oxide (ITO) -coated glass, it is expected to have various applications in, for example, magnetic recording media, sensors, and templates for preparing one-dimensional nanostructures on the substrates. It has been reported that anodic porous alumina is formed on substrates by forming an Al film by sputtering or thermal evaporation and subsequent anodization in an acidic solution.…”
mentioning
confidence: 99%